Experience in the implementation of accounting harmonization in public organizations - Diaz Martinez, Claudia; Hernandez Madrigal, Monica; Ramirez Flores, Elfego; Hernandez Garcia, Patricia (RAN - Revista Academia & Negocios, 2023)
Purpose: The main purpose of this paper is to analyze the accounting harmonization practices of decentralized public organizations in the city of San Luis Potosí, Mexico. Method: Through a non-experimental, cross-sectional, descriptive and correlational study, a questionnaire was applied to a sample of 63 decentralized agencies. The results highlight the importance of a harmonized government accounting system in compliance with the federal entity in terms of accounting harmonization. Implications: While the importance of harmonization practices is recognized, there are obstacles to their implementation such as insufficient staff, poor communication, lack of funds, and lack of sanctions. Originality: This research project contributes to the literature by offering a diagnosis that promotes accounting harmonization practices in the public sector.